Resveratrol blocks atherosclerosis development by inhibiting IL-1β in macrophages induced by cholesterol - Xie Yilin (Archives of Biological Sciences, 2019)
Resveratrol is a polyphenolic compound that exhibits antiinflammatory and cardioprotective properties. In this study we investigated the protective role of resveratrol on the inflammatory activation of macrophages during pathogenesis of atherosclerosis. Macrophage Ana-1 cells were stimulated by cholesterol and resveratrol, and the cell culture supernatant was collected to treat human umbilical vein endothelial cells (HUVECs). The release of IL-1β into the Ana-1 cell supernatant was quantified by ELISA. Expression of the adhesion molecule ICAM-1 and E-selectin in HUVECs were examined by Western-blotting. Additionally, the adhesion of monocytes in HUVECs under different conditions was tested by cell adhesion analyses. The results indicated that the high cholesterol treatment increased the expression level of IL-1β, while pretreatment with resveratrol inhibited this induction of IL-1β in Ana-1 cells. Resveratrol inhibited the adhesion of monocytes to the endothelium at least partly through inhibition of IL-1β expression in macrophages. Moreover, the expression level of caveolin-1 significantly increased after the pretreatment with resveratrol, indicating that resveratrol enhances reverse cholesterol transport (RCT) in macrophages. Our study indicated that resveratrol has significant antiinflammatory effects and can be considered as a candidate molecule to prevent atherosclerosis.